The cross-linguistic influence of Arabic Language on the English Language writing: A case study of Misrata Secondary School - Lghzeel, Fatma Ali Mohamed; Noor Raha, Mohd Radzuan (2018)
It is definitely not easy to explain cross-linguistic influence – considering how complex of a phenomenon it is, but fascinating at the same time, and because of that fact it has grabbed the attention of many researchers and scholars. As soon as a speaker becomes bilingual, the new language will very subtly influence the native one, even if it is not much used. This is how first language attrition may start. This modest paper studied one of the issues that foreign language learners encountered, which is the negative effects of the native language (NL) on the overall learning of the target language (TL), focusing on the influence of the mother tongue on learning the English skills (listening, speaking, reading and writing); specifically, in writing. The researcher aimed to examine the obstacles faced by learners of the target language and as well as their attempts in minimising the problem. The research intends to find out whether the English language is influenced by Arabic language in terms of using the ideas and Arabic techniques in writing paragraphs. We enriched the paper with five detailed chapters relevant to this issue. Thirty-two participants were involved in the task of writing a paragraph which is part of an informal letter. In addition, they were given a sample and typical expressions in order to help them with the task as required. Furthermore, they were observed daily for sufficient months. The results revealed that for the observation and writing tasks; the majority of the participants had problems in writing including; literal translation, disorganising ideas, illogical sentences, and some grammatical mistakes. Lastly, those difficulties were positioned under three categories; namely syntactic, semantic and rhetorical reference errors for analysis and discussion purposes.